Caractérisation du potentiel antagoniste de la flore Pseudomonas rhizosphérique vis - à- vis des phytopathogènes - BOURAHLA, Nesrine; MIMOUNI, Halima Esaadia (My University, 2023)
Rhizosphere bacteria play an important role in controlling plant pathogenic fungi and enhancing plant growth through a wide variety of mechanisms. Our study focused on the research and selection of these bacteria, twenty-four isolates were isolated from the rhizosphere of different plants grown in the region of Safsaf and Achâacha. The isolates were tested to assess their antagonistic potency against ten phytopathogenic fungi. They are also tested for their ability to produce cell wall degrading enzymes (pectinase; amylase; cellulase) as well as PGP-related activities (AIA and phosphate solubilization). The results showed that the majority of isolates present antagonistic activity against phytopathogenic fungi. Most isolates have the ability to produce hydrolytic enzymes (cellulase and amylase), and for the enzyme pectinase all 33 isolates were unable to produce this enzyme. Four isolates were able to solubilize phosphate. Eight isolates were productive of indole acetic acid. The set of PGP characters of the various isolates studied in the present study suggest that these microorganisms can promote plant growth.
Keywords: rhizosphere; PGP; AIA; phosphate; pectinase; amylase; cellulase